Awareness of Health Workers in Premature Units At Kirkuk City Hospitals Concerning Neonatal Jaundice (Indian Journal of Forensic Medicine & Toxicology, 2020)
Objective: this study aimed to assess the awareness of the health workers in premature units regardingneonatal jaundice at Kirkuk city hospitals, as well as to find out the socio demographic characteristics of thestudy sampleMethodology: A descriptive study was carried out at premature units of Azadi Teaching Hospital, KirkukGeneral Hospital and Pediatric Hospital of Kirkuk city, for a period from the 1st February and up to the 15thof May, 2019 and to achieve the objectives of the study. A non-probability (purposive) sample of (62) healthworkers working at premature unit were recruited. Developed questionnaire was constructed for the purposeof the study which consisted of two parts: the demographic characteristics; awareness part (knowledge andpractices). The data were collected through the use of self- administered technique. They were analyzedthrough the application of descriptive statistical analysis (Frequency, Percentage % and mean score) dataanalysis.Results: The findings of the study indicated that (45.2%) of the staff were from pediatric hospital. (40.3%)were graduated from Nursing Institute, (43.5%) had experience from 1<5 years and (74.2%) had participatedin a training course mostly inside the country. The total grand mean score for the staff awareness (knowledgeand practices) were adequate (1.73).Conclusions and Recommendations: Assessment for the study sample awareness was adequate.Educational programs should be designed to increase the health workers awareness working at pediatricdepartments regarding management of neonatal jaundice especially those with less than 5 years’ experience.